2001
DOI: 10.1046/j.1528-1157.2001.042007837.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe Myoclonic Epilepsy of Infancy: Extended Spectrum of GEFS+?

Abstract: Summary:Purpose: Severe myoclonic epilepsy of infancy (SMEI) is an intractable epilepsy of early childhood of unknown etiology. It is often associated with a family history of seizure disorders, but epilepsy phenotypes have not been well described. We sought to characterize the seizure phenotypes of relatives to better understand to the genetic basis of SMEI.Methods: Probands with SMEI were identified, and systematic family studies were performed. Epilepsy syndromes were characterized in affected family member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
118
0
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(132 citation statements)
references
References 31 publications
3
118
0
11
Order By: Relevance
“…We have shown that hyperthermia does not interfere with the trafficking of rescued Na v 1.1-R1916G and thus it should not be a mechanism implicated in the generation of FS in this family, differently from some GEFS+ GABA-A receptor mutants (Kang et al, 2006) The almost complete loss of function of Na v 1.1-R1916G that we have observed in some conditions is consistent with the possibility that this mutation could cause severe phenotypes if in vivo the rescuing interactions are inefficient. Phenotypic variability is expected in GEFS+ families (Scheffer and Berkovic, 1997), but the phenotypic spectrum is still uncertain in particular regarding severe phenotypes (Singh et al, 2001). Our data raise the risk that in the descendants of the family under study a very severe phenotype (e.g.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We have shown that hyperthermia does not interfere with the trafficking of rescued Na v 1.1-R1916G and thus it should not be a mechanism implicated in the generation of FS in this family, differently from some GEFS+ GABA-A receptor mutants (Kang et al, 2006) The almost complete loss of function of Na v 1.1-R1916G that we have observed in some conditions is consistent with the possibility that this mutation could cause severe phenotypes if in vivo the rescuing interactions are inefficient. Phenotypic variability is expected in GEFS+ families (Scheffer and Berkovic, 1997), but the phenotypic spectrum is still uncertain in particular regarding severe phenotypes (Singh et al, 2001). Our data raise the risk that in the descendants of the family under study a very severe phenotype (e.g.…”
Section: Discussionmentioning
confidence: 84%
“…SMEI is a very severe drug-resistant epileptic encephalopathy characterized by frequent seizures, ataxia, slowed psychomotor development, mental decline and high mortality rate (Dravet et al, 2005), and is caused by mutations of Na v 1.1 that often cause complete loss of function (Claes et al, 2001;Meisler and Kearney, 2005). Most SMEI mutations arose de novo, but in few cases they have been inherited from mildly affected parents (Nabbout et al, 2003) and a family history of epilepsy has been observed in some SMEI cases; thus, it has been proposed to extend the GEFS+ spectrum including SMEI as the most severe phenotype (Singh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Most SMEI mutations arose de novo, but in few cases, they have been inherited from mildly affected parents (Claes et al, 2001;Nabbout et al, 2003). A family history of epilepsy has been reported for some SMEI cases, and it has been proposed to extend the GEFSϩ spectrum including SMEI as the most severe phenotype (Singh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GEFSϩ families show a large phenotypic variability that ranges from mild phenotypes to very severe ones (Scheffer and Berkovic, 1997). Thus, it has been hypothesized that genetic background could modulate disease severity modifying the properties of the mutant protein (Singh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in SCN1A, located in 2p24.3, were initially identified in families with an autosomal dominant condition termed generalized epilepsy with febrile seizures-plus (GEFS+; MIM# 604233) [Escayg et al 2000]. In GEFS+, there is also a variable association of prolonged febrile seizures with different types of afebrile seizures types, which are nonetheless mild, in comparison to SMEI, and generally responsive to treatment Singh et al 2001]. The first SCN1A mutations detected in patients with GEFS+ were missense mutations, whereas those found in SMEI introduced premature stop codons in SCN1A.…”
Section: Introductionmentioning
confidence: 99%